Prevenção de deficiência: programa de formação para professores Kaingang na terra indígena Ivaí-Paraná - Buratto, Lúcia Gouvêa (2010)
Many health problems and deficiencies of Kaingang indigenous that in many cases are illness sequels, that are the results of occupation process of their lands, where they were obligated to agglomerate themselves in villages without minimum sanitarium conditions putting them in vulnerability situation for many parasitic diseases, bacterial and viral. The contact propitiated the introduction of alcohol drinks and sexually transmissible diseases and other contagious pathologies that cause diseases too. Besides the indigenous begin to have children in their adolescence, the drugs as cigarette and mainly alcohol are consumed for the most of adolescents. There are still suicide cases among teenagers, adults and children with many types of deficiency such as: mental, physical, auditory, visual and multiple. The present study aims at training Kaingang teachers to act in the deficiencies prevention. Ten teachers attended the Kaingang ethnicity that obeyed the established criteria. It was used two valuation ways: a) a questionnaire to know the number of the incidence of deficiency cases; b) pre and post questionnaires application of the prevention program. Bilingual materials were produced (Portuguese and Kaingang). The informations were organized and showed in figure and graph. According to the results of the incidence of deficiency cases were found that Indigenous Land Marrecas 27 cases, Ivaí 23 and Faxinal 11. Referring to the information comparison among pre and post questionnaires, it was obvious the efficacy of the application of prevention program. The informations achieved in the post questionnaire show relevant results referring to the subjects acquisition and experiences provided by this program. Other relevant point was the contribution of the bilingual material which facilitated the accessibility to the information about deficiencies prevention. It may be considered that this present study show results which will take in account in the formulation of public policy for indigenous people and they can generate more effective and appropriate procedures and actions to Sociocultural organization of Kaingang.